Assessment of subclinical hypertention-mediated heart damage in young adults with connective tissue dysplasia - M. I. Shupina; Yu. V. Tereschenko; V. V. Potapov; G. I. Nechaeva (Лечащий Врач)
In order to assess the features of hypertension-mediated heart damage in young adults with hypertension and connective tissue dysplasia (СTD), an echocardiographic examination of 574 people aged 18 to 29 years was performed. It was revealed that young adults with hypertension and CTD have lower levels of the interventricular septum and left ventricle walls thickness, left ventricle mass and its indexes than in hypertensive patients without CTD, and these parameters do not reach the generally recognized upper limit of the norm. This leads to systematic underdiagnosis of hypertension-mediated heart damage, incorrect assessment of the stage of hypertension, and inadequate management for these patients.